Rational design of promising candidates for photoactive layer in polymer solar cells: Insights from computation - Orenha, Renato P.; Ramos, Salvador B. [UNESP]; Natal, Maria L. L.; Gomes, Márcio H. A.; Muñoz-Castro, Alvaro; Madureira, Letícia M. P.; Caramori, Giovanni F.; Piotrowski, Maurício J.; Parreira, Renato L. T. (Wiley, 2024)
The design of organic solar cells, OSCs, requests a more efficient configuration of photoactive layers composed of p-type (quinoxaline, Qx) and n-type (naphthalene diimide, NDI) semiconductors that enable light harvesting along with a high-power conversion efficiency. Here, Qx-(phenyl or Ph) and NDI structures have been modulated using both electron withdrawing (EWG) and electron donating (EDG) groups such as −F, −NHCOCH3, −OCH3, −OH, −CHO, −COOCH3, −COOH, −CN, −SO3H, and −NO2, aiming to design an effective photoactive p-n layer. The HOMO-LUMO gap of Qx-Ph can be tuned to the visible light spectrum by the addition of EWG in the Qx ring (decreasing the LUMO energy) and by EDG in the Ph ring (increasing the HOMO energy). The analyzed complexes show key electronic properties in organic solar cells with large power conversion efficiency. Descriptive data analysis suggests that the magnitude of the non-covalent interactions in donor (Formula presented.) acceptor (D (Formula presented.) A) complexes is expected to play a role in the efficiency of OSCs. The results will contribute to a more effective design of the photoactive layer in OSCs.
Keywords: descriptive data analysis; EDA; FMOs; organic solar cells; power conversion efficiency